PENGARUH SISTEM PENGUPAHAN TERHADAP KINERJA PEGAWAI KERJA MUSIMAN DI PTPN X(PABRIK GULA CAMMING) KABUPATEN BONE - Andi Arwin Mustafa; Muhlis Madani; Nuryanti Mustari (Kolaborasi : Jurnal Administrasi Publik, 2018)
The aims of this research is to determine the wage level about wage system and the effect of the wage system towards the performance of seasonal employees in PTPN X (Sugar Factory of Camming Bone). The research applied descriptive qualitative type. The population of this study involves all the seasonal workers of the grinding section which consist of 65 employees as the samples. The results of this study indicate that the wage system reaches 79.2% or it is in good category andthe employees performance reaches 83% or is in very good category. Later, based on the results of the hypothesis test, itindicates that there is a significant influence between the wage system and the performance of seasonal employees in PTPN X (Sugar Factory of Camming Bone). Keywords: wage system, employee performance